IMBAL: SEBUAH IDE PENCIPTAAN KOMPOSISI MUSIK DALAM PERANGKAT CALUNG - Hadi Boediono (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2013)
The idea of Imbal was inspired when saw on the development of Calung in Banyumas. A development perceived as an element of â€œcoercionâ€, ie forcing together two cultures, two different tone system, but there is absolutely no aesthetic considerations. Seeing this phenomenon, the composer want to make a few possibilities that can be done on calungâ€™s instrument, such as the beat pattern and interlocking patterns on the basic of existing techniques.Key words: Calung-ideas Musical composition